Synthesis, Characterization, and Photocatalytic Activity of N-Doped ZnO/ZnS Composites - Hongchao Ma; Xiaohong Cheng; Chun Ma; Xiaoli Dong; Xinxin Zhang; Mang Xue; Xiufang Zhang; Yinghuan Fu (International Journal of Photoenergy)
The aim of the present study is to enhance photocatalytic performance of ZnO semiconductor by comodification with doping of nonmetal ions and coupling with another semiconductor. Therefore, we synthesized the N-doped ZnO/ZnS photocatalysts via a simple heat-treatment approach using L-cysteine as N and S source in this work. Anthraquinone dye (reactive brilliant blue KNR) is employed as the model contaminants to evaluate the photocatalytic activity of as-synthesized samples under sunlight illumination. The N-doped ZnO/ZnS synthesized by this method shows better photocatalytic activity as compared to that of pure ZnO. The enhanced photocatalytic activity of the N-doped ZnO/ZnS composites may be related to the existence of N doping, ZnS/ZnO heterostructure, and covered abundant carbon species on the photocatalyst surface, which causing high absorption efficiency of light, efficient separation of electron-hole pairs, and quick surface reaction in doped ZnO.